IMPLIKASI APLIKASI SISTEM TEKNOLOGI INFORMASI DALAM PELAKSANAAN MANAJEMEN KUALITAS - Kunto Wibisono (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2007)
The basic aim of this research is to examine the effect of information technologyon quality management. Sample of this research take place in 5 travel agentcompanies, 2 membership card companies, 4 education companies, and 3manufactures companies that used internet and website design for promoting theirproduct and services. In analyzing the data, researcher used paired sample t test.The result indicates there are significant relationship among used of informationtechnology and not used an information technology. That’s like a t heory said thatinformation technology gives a positive effect to company especially in qualitymanagement.The findings obtained in this research are expected could be used as asupplement reference for company, especially for specific company that willimplicated information technology.